Extensive Listening and Viewing in EFL Learning: A Systematic Literature Review - Christin Natalia Pajow; Nengah Nita Loktika (CV Wahana Publikasi, 2026)
The growing accessibility of digital technologies has transformed how English as a Foreign Language (EFL) learners engage with authentic language input, particularly through Extensive Listening (EL) and Extensive Viewing (EV). As input-based approaches, EL and EV provide sustained exposure to meaningful auditory and audiovisual materials that may facilitate language acquisition beyond traditional classroom instruction. However, despite growing interest in EL and EV, existing evidence remains fragmented, resulting in limited integrated understanding of their implementation, linguistic and affective outcomes, technology-mediated resources, and challenges and future research directions in EFL contexts. Therefore, this study systematically reviews and synthesizes recent research on EL and EV published between 2021 and 2026. Following the Systematic Literature Review (SLR) procedures proposed by Kitchenham et al. (2007) and the PRISMA guidelines, twelve peer-reviewed articles from Scopus-indexed and SINTA-accredited journals were selected and analyzed. The findings revealed that EL and EV were predominantly implemented among undergraduate EFL learners through sustained exposure to authentic and multimodal input. Positive outcomes were reported in listening comprehension, vocabulary acquisition, pronunciation awareness, listening fluency, motivation, confidence, engagement, and learner autonomy. Technology-mediated resources, particularly YouTube, supported flexible access to authentic language exposure, while future studies emphasized broader learner populations and longitudinal designs. To conclude, the findings suggest that EL and EV may support language acquisition in EFL contexts through sustained exposure to authentic and multimodal input within technology-mediated learning environments.